Lipid Profile of Xylella fastidiosa Subsp. pauca Associated With the Olive Quick Decline Syndrome - Scala, Valeria; Reverberi, Massimo; Salustri, Manuel; Pucci, Nicoletta; Modesti, Vanessa; Lucchesi, Simone; Loreti, Stefania (Frontiers in Microbiology, 2018)
Lipids, components of the plasma and intracellular membranes as well as of droplets, provide different biological functions related to energy, carbon storage and stress responses. Bacterial species display diverse membrane compositions that changes in response to the different environmental conditions. During plant-pathogen interactions, lipids might have roles in several aspects such as recognition, signal transduction and downstream responses. Among lipid entities, free fatty acids and their oxidized form, the oxylipins, represent an important class of signalling molecules in host-pathogen perception, especially related to virulence and defence. In bacteria, free fatty acids (e.g. diffusible signalling factors) and oxylipins have a crucial role in modulating motility, biofilm formation and virulence. In this study, we explore by LC-TOF and LC-MS/MS the lipid composition of X. fastidiosa subsp. pauca strain De Donno in pure culture; some specific lipids (e.g. ornithine lipids and the oxylipin 7,10-diHOME), characteristic of other pathogenic bacteria, were revealed. Nicotiana tabacum was used for testing the ability of this pathogen in producing such lipids in the host. Different lipid compounds present a clear distribution pattern within the infected plant tissues compared to the uninfected ones